ANALISIS KINERJA KEUANGAN PADA KOPERASI PEGAWAI NEGERI BADAN METEOROLOGI, KLIMATOLOGI, DAN GEOFISIKA - Ade Caswito; Lisdiana Lisdiana; Dwi Listiawati; Putri Mutiara Qalbi; Yoan Rivaldhi Ada (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: This study analyzes the financial performance of the BMKG (National Cooperatives and BMKG) for the 2023–2024 period as a basis for evaluating the cooperative's health and aspirations. The analysis is necessary to assess the effectiveness of accountable financial management amidst increasing competition. The assessment is based on soundness standards.Methods: The quantitative descriptive method uses the 2023–2024 financial statements to calculate profitability, liquidity, and solvency ratios and then compares them to standards.Results: The results showed a healthy NPM and increased from 49.43% (2023) to 51.51% (2024). Unhealthy ROA decreased from 3.97% to 3.92%, while unhealthy ROE decreased from 7.92% to 7.75%. Liquidity weakened: Current Ratio 144.75%→138.11% and Quick Ratio 143.06%→136.99% (unhealthy), Cash Ratio 40.31%→48.38% (very unhealthy). Solvency was quite healthy: DAR 45.9%→45.6% and DER 91.5%→90.2%.Conclusion and suggestion: The KPN BMKG's financial performance in 2023–2024 was quite good: NPM was healthy, and solvency was quite healthy. However, ROA and ROE were suboptimal, and liquidity, particularly cash, was unhealthy. Strengthen cash management, accelerate receivables collection, optimize assets and equity, and control liabilities to ensure a healthier and more sustainable cooperative. Keywords: KPN BMKG, Cooperative Financial Performance, Profitability Ratio, Liquidity Ratio, Solvency Ratio